Health, Income, and Measures of Inequality – Why Inequality May Decline When All Inequality Measures Indicate the Opposite - Kjell Arne Brekke; Snorre Kverndokk (CESifo GmbH, 2024)
We study how measures of socioeconomic health inequality inform about welfare inequality. We argue that transfers of either income or health from a better off to a worse off individual should reduce welfare inequality. Lacking an objective measure of individual welfare, we suggest that such a transfer should reduce at least one measure of inequality: inequality in income, health or socioeconomic health. This puts restrictions on measures of socioeconomic health inequality, where a correlation between income and health meets the requirement, while the concentration index only meets the requirement in a statistical sense. Finally, we show empirically that changes in the concentration index over time can be dominated by changes in income. Using data from HUNT, income changes account for 90% of the changes in the concentration index, while health and income are equally important with data from EU-SILC, with large variation across countries and years.
Keywords: D31; I12; 330; socioeconomic inequality; health inequality; health transfers; income transfers; concentration index